1969
DOI: 10.1530/jrf.0.0180121
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Capacity in Gilts

Abstract: A review of the literature indicates that injection of gonadotrophic hormones or giving high-level-energy feeds will markedly increase the number of ovulations in polytocous animals. Higher ovulation rates are then followed by an increase in the percentage of embryos which die in utero. This increased embryonic death may be due either to inherent limitations within the individual embryo or to maternal limitations which affect the litter (Runner, 1951). In any event, the number of young at term remains at a lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 11 publications
(6 reference statements)
1
24
0
Order By: Relevance
“…They are in agreement with the concept of uterine capacity demonstrated through superovulation with a PMSG treatment of sows [12,33,41] or superinduction, adding embryos to recipient pregnant sows [3,4,19,42]: despite a much higher ovulation rate per uterine horn in the HHO than in the CTR group, litter size at term is not different. According to Webel and Dziuk [54], Knight et al [31] or Chen and Dziuk [9], foetal death related to uterine capacity occurs after day 25 of gestation.…”
Section: Effect Of Treatments On Reproductive Performance and Ubfsupporting
confidence: 84%
See 1 more Smart Citation
“…They are in agreement with the concept of uterine capacity demonstrated through superovulation with a PMSG treatment of sows [12,33,41] or superinduction, adding embryos to recipient pregnant sows [3,4,19,42]: despite a much higher ovulation rate per uterine horn in the HHO than in the CTR group, litter size at term is not different. According to Webel and Dziuk [54], Knight et al [31] or Chen and Dziuk [9], foetal death related to uterine capacity occurs after day 25 of gestation.…”
Section: Effect Of Treatments On Reproductive Performance and Ubfsupporting
confidence: 84%
“…The limitation of litter size, called uterine capacity [3], is characteristic of the genotype and of the animal. For instance, the efficiency of the uterus is higher in hyperprolific Large-White × Meishan than in standard Large White sows [32].…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines and NO are essential to placental growth and angiogenesis, thereby regulating the placental-fetal blood flow and the transfer of nutrients, oxygen, ammonia, and metabolic waste between mother and fetus in pregnant mammals (Bird et al 2003;Wu et al 1998bWu et al , 2009). Importantly, the size and functional capacity of the placenta, and uteroplacental transfer of materials between mother and fetus, were the major factors to affect embryonic/fetal growth and development (Bazer et al 1969;Gude et al 2004;Wu et al 2006Wu et al , 2010. Previous reports have shown that placental efficiency affects litter size and that placental size is highly correlated with fetal weight after day 60 of gestation in swine (Biensen et al 1998;Wilson et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Uterine capacity is defined as the maximal number of fetuses that the uterine environment can support to birth (Bazer 1969). Whereas in the Afec Awassi, litters of four or more are very rare-about 2%, in the Afec Assaf they comprise about TMY total milk yield through the lactation, DMY daily milk yield, PWMY post-weaning milk yield 15% of the litters (Gootwine et al 2008).…”
Section: Gene Introgressionmentioning
confidence: 99%